Fusarium sudanense, endophytic fungus causing typical symptoms of seedling blight and seed rot on wheat - Larrán, Silvina (2020)
An endophytic fungus isolated from healthy wheat seeds cultivar Klein Yarará in Buenos Aires Province, Argentina, was initially identified as belonging to the Fusarium fujikuroi species complex based on morphological and cultural characteristics. The fungus role in pathogenicity was investigated by artificial inoculation of wheat seeds. Symptoms evaluated 7 and 14 days after inoculation showed that the fungus was pathogenic on seed and seedlings causing symptoms as seed decay, seedling blight and seed rot. The fungus was re-isolated to fulfill Koch’s Postulates and was identified as F. sudanense (strain LBEA 3100), a new species recorded in Argentina. The fungal identity was corroborated using molecular techniques by sequencing the ITS region, D1/D2 domains of the LSU gene and TEF-1 alpha region and by comparison with international databases. Ecophysiological studies of F. sudanense (LBEA 3100) performed at different water activities and temperatures showed faster growth rate at the highest water activity and 25 C. This is the first report of F. sudanense, isolated from healthy wheat seeds, causing typical symptoms of seedling blight and seed rot on wheat.